Microglia in Health and Disease: The Strength to Be Diverse and Reactive - Uriarte Huarte, Oihane; Richart, Lorraine; Mittelbronn, Michel; Michelucci, Alessandro (Frontiers in Cellular Neuroscience, 2021)
Microglia are the resident immune effector cells of the central nervous system (CNS) rapidly reacting to any perturbation in order to maintain CNS homeostasis. Although their outstanding reactive properties have been elucidated over the last decades, their heterogeneity in healthy tissue, such as across brain regions, as well as their diversity in the development and progression of brain diseases, are currently opening new avenues to understand the cellular and functional states of microglia subsets in a context-dependent manner. Here, we review the main breakthrough studies that helped in elucidating microglia heterogeneity in the healthy and diseased brain and might pave the way to critical functional screenings of the inferred cellular diversity. We suggest that unraveling the cellular and molecular mechanisms underlying specific functionalities of microglial subpopulations, which may ultimately support or harm the neuronal network in neurodegenerative diseases, or may acquire pro- or anti-tumorigenic phenotypes in brain tumors, will possibly uncover new therapeutic avenues for to date non-curable neurological disorders.